2009
DOI: 10.1111/j.1365-2702.2008.02740.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma as a predictor of eating psychopathology and its mediating variables in patients with eating disorders

Abstract: Early intervention for childhood trauma and depression might contribute to preventing eating disorders in traumatised individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 45 publications
5
98
0
5
Order By: Relevance
“…For instance, childhood physical abuse (CPA) and childhood sexual abuse (CSA) have been associated with dissocial and impulsive traits in BN (Steiger et al, 2010), borderline personality disorder (Steiger et al, 1996), and submissiveness (Leonard et al, 2003). Moreover, recent reports suggest that childhood emotional abuse (CEA) is related to eating-disorder symptom severity, and to comorbid depression, affective instability, impulsivity and felt ineffectiveness (Kong and Bernstein, 2009;Groleau et al, 2012).…”
Section: Bn and Childhood Abusementioning
confidence: 96%
“…For instance, childhood physical abuse (CPA) and childhood sexual abuse (CSA) have been associated with dissocial and impulsive traits in BN (Steiger et al, 2010), borderline personality disorder (Steiger et al, 1996), and submissiveness (Leonard et al, 2003). Moreover, recent reports suggest that childhood emotional abuse (CEA) is related to eating-disorder symptom severity, and to comorbid depression, affective instability, impulsivity and felt ineffectiveness (Kong and Bernstein, 2009;Groleau et al, 2012).…”
Section: Bn and Childhood Abusementioning
confidence: 96%
“…Thus it appears when the psychological consequences of difficult experiences are unresolved and persist into adulthood, these experiences may predispose individuals to eating pathologies (Kong and Bernstein, 2008). This interpretation aligns with explanations of attachment insecurity, where psychological histories are implicated in the association between attachment and emotional eating.…”
Section: Predicting Emotional Eating From Psychological Symptom Distressmentioning
confidence: 56%
“…Although research has demonstrated childhood traumas (e.g., emotional and/or physical neglect) are frequently reported in eating disordered populations, researchers (Kong and Bernstein, 2008) suggest negative psychological affect, rather than the traumatic experience itself, may be key to emotional eating tendencies. Thus it appears when the psychological consequences of difficult experiences are unresolved and persist into adulthood, these experiences may predispose individuals to eating pathologies (Kong and Bernstein, 2008).…”
Section: Predicting Emotional Eating From Psychological Symptom Distressmentioning
confidence: 99%
“…Exposure to trauma may contribute to general psychobiological dysregulation, which could increase vulnerability to a number of psychiatric disorders (Yehuda, 2001). Furthermore, a number of recent studies have identified emotion dysregulation (Michopoulous, Powers, Moore, Villarreal, Ressler, & Bradley, 2015;Mills, Newman, Cossar, & Murray, 2014;Racine & Wildes, 2015) and depression (Michopoulos et al, 2015;Kong & Bernstein, 2009) as mediators in the relationship between childhood trauma exposure and disordered eating in adulthood. In particular, emotional abuse has been strongly implicated in the prediction of emotion dysregulation (Kong & Bernstein, 2009;Racine & Wildes, 2015) and emotional maltreatment is an increasingly identified form of childhood maltreatment in Canada.…”
Section: Trauma Historymentioning
confidence: 99%
“…Furthermore, a number of recent studies have identified emotion dysregulation (Michopoulous, Powers, Moore, Villarreal, Ressler, & Bradley, 2015;Mills, Newman, Cossar, & Murray, 2014;Racine & Wildes, 2015) and depression (Michopoulos et al, 2015;Kong & Bernstein, 2009) as mediators in the relationship between childhood trauma exposure and disordered eating in adulthood. In particular, emotional abuse has been strongly implicated in the prediction of emotion dysregulation (Kong & Bernstein, 2009;Racine & Wildes, 2015) and emotional maltreatment is an increasingly identified form of childhood maltreatment in Canada. A recent study found that emotional maltreatment is detected nearly twice as often in situations where abuse and neglect is also reported and emotional abuse reports are two to three times more frequent than reports of emotional neglect (Chamberland, Fallon, Black, & Trocmé, 2011).…”
Section: Trauma Historymentioning
confidence: 99%